(untitled) (Journal of Hama University, 2024)
The research aims to show the effect of the financial solvency of the National Insurance Company NIC on the investment activity in it, as the research assumes the existence of a statistically significant relationship for each of the independent variable (solvency) in the dependent variable (investments of the insurance company) measured by the following variables: (financial investments at fair value , rate of return on investment) by using the simple regression analysis method to study the relationship between the independent variable and each dependent variable, and based on the statistical analysis program SPSS. The researcher took the National Insurance Company as a place to conduct the research, as it has good financial solvency, and the company’s financial statements for the period (2016-2021) were relied on, and the annual reports issued by the Insurance Supervisory Authority. The study concluded that there is a direct relationship, but it is not statistically significant for each From financial solvency and (financial investments at fair value and rate of return on investment.( One of the most important findings of this study is that the National Insurance Company enjoyed a high level of financial solvency that qualifies it to fulfill its obligations towards its clients, in addition to a cash surplus that enables the company to operate it in various investment fields to achieve additional profits, There is no statistically significant effect of solvency in financial investments at fair value and return on investment in the National Insurance Company NIC, and the relationship is positive.